The evaluation of World Vision's Area Development Programme in Lesotho : the case of Taung - Motsomi, Napo F. (Napo Francis) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPA)--University of Stellenbosch, 2003.